Kontribusi Minat Baca dan Bimbingan Belajar Orangtua terhadap Prestasi Belajar Siswa Sekolah Dasar - Mulyati Mulyati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2004)
This research is intended to determine whether or not there is a correlation between reading interest and parents’guidance in learning and the students’ learning achievement, either separately or simultaneously. The correlational research was conducted from April to August 2000. The population was students of the State Elementary Schools (SDN) in the District of Laweyan Surakarta in the 1999/2000 academic year. The sample was 30 students taken using stratified random sampling technique. A questionaire is used to measure reading interest and  parents’ guidance in learning. The data of the students’ achievements were collected by using documentation. Data were anaysed using correlation and regression. The result shows that: (1) there is a positive correlation between reading interest and students’ achievement  (r = .93) and a liner regression equation of Y = 1.080 + .072X1; (2) there is a positive correlation between parents’ guidance and students’ achievement  (r = .94) and a linear regression of Y = 2.121 + .061 X2,; (3) there is a simultaneous correlation between reading interest,  parents’ guidance in learning and the students’  achievement (R = .92) and a linear regression of Y  =  1.345+ .036 X1 + .033X2.Key words: learning achievement, reading interest, parent guidance.